Pengaruh Struktur Modal dan Modal Intelektual terhadap Kinerja Keuangan Perusahaan (Studi Kasus Pada Perusahaan Sektor Barang Konsumen Primer) - Putra, Achmad Yasfi Ramadhana; Irawati, Zulfa (Paradoks : Jurnal Ilmu Ekonomi, 2025)
Companies experience competitive competition in this era of globalization, forcing companies to innovate technology and change the patterns of running their businesses. Companies are required to innovate quickly so that they are expected to provide increased value for the entity. Tight company competition has an impact on good performance and company excellence so that the company can successfully achieve its goals as set by Hidayat & Pamungkas (2023). The data collection method used in this study is the documentation method. This method is carried out by examining an organization's documents to detect changes during a certain period. The data used are in the form of annual financial reports of primary consumer goods sector companies published by the Indonesia Stock Exchange (IDX) and related company websites.